2020
DOI: 10.5588/ijtld.20.0278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic obstructive pulmonary disease and smoking on the outcome of COVID-19

Abstract: OBJECTIVE: To investigate the association between chronic obstructive pulmonary disease (COPD) and smoking with outcome in patients with COVID-19.METHODS: A systematic literature search was performed using PubMed, EuropePMC, SCOPUS and the Cochrane Central Database. A composite of poor outcome, mortality, severe COVID-19, the need for treatment in an intensive care unit (ICU) and disease progression were the outcomes of interest.RESULTS: Data on 4603 patients were pooled from 21 studies. COPD was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
72
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 0 publications
6
72
0
2
Order By: Relevance
“…Analysis for heterogeneity was limited due to the fact that only two studies reported comorbidities that are associated with increased mortality in COVID-19 patients. These comorbidities are obesity (OR 1.55), hypertension (OR 2.21), diabetes (Risk Ratio [RR] 2.38), cardiovascular diseases (RR 2.25), and chronic obstructive pulmonary disease (OR 4.36) ( Huang et al., 2020 ; Pranata et al., 2020b , c ; Pranata, Lim, Huang, Raharjo & Lukito, 2020a ; Pranata, Huang, Lim, Wahjoepramono & July, 2020d ). Ideally, exploration of heterogeneity can be performed using meta-regression, however, it cannot be performed due to the lack of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis for heterogeneity was limited due to the fact that only two studies reported comorbidities that are associated with increased mortality in COVID-19 patients. These comorbidities are obesity (OR 1.55), hypertension (OR 2.21), diabetes (Risk Ratio [RR] 2.38), cardiovascular diseases (RR 2.25), and chronic obstructive pulmonary disease (OR 4.36) ( Huang et al., 2020 ; Pranata et al., 2020b , c ; Pranata, Lim, Huang, Raharjo & Lukito, 2020a ; Pranata, Huang, Lim, Wahjoepramono & July, 2020d ). Ideally, exploration of heterogeneity can be performed using meta-regression, however, it cannot be performed due to the lack of studies.…”
Section: Discussionmentioning
confidence: 99%
“…22 Nevertheless, there are several factors that commonly coexists in patients with hip fracture, namely advanced age, obesity, and various comorbidities which are associated with increased severity and mortality of COVID-19. 8e11, 14,15,29,30 Because of reduced functional reserves and weakened immune function, these individuals are more adversely affected by SARS-COV-2 infection. The poor prognosis can be attributed to a combination of these factors rather than purely attributed to a single factor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the presence of more than three pre-existing comorbidities, smoking, which is associated with increased severity in COVID-19, was found to independently increase postoperative mortality rates in COVID-19 patients. 7,14 After surgery, thromboembolic events can occur in patients due to restricted mobility. In certain cases, postoperative pulmonary complications could be observed within a few days or weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older individuals and those with underlying comorbidities, such as hypertension, diabetes, cardiovascular and cerebrovascular diseases, coagulopathy, kidney and liver problems, and chronic lung disease, are categorized as high-risk groups for contracting severe COVID-19 [25][26][27][28][29][30][31][32]. Under such a pandemic, they are forced into social isolation and quarantine at home, and most of these individuals are being physically inactive and mentally stressed (e.g., depression and anxiety) [33].…”
mentioning
confidence: 99%